Rancang Bangun Aplikasi E-Rekrutmen Karyawan Baru Berbasis Online Menggunakan Metode SMART - Kamil, Muhammad Ihsan (LPPM Universitas Al Washliyah Labuhanbatu, 2023)
This observation activity is to investigate e-recruitment or digital recruitment carried out through PT. Eternal gentle Nabila. Furthermore, this study also aims to determine the benefits and influences felt by the organization after using the Recruitment approach. The research technique used in this study is a qualitative-descriptive method to explain the conditions of recruitment. The information obtained in this study uses commentary units, interviews and documentation studies. The effect of this display implies that the presence of Recruitment has contributed to providing high quality profits for PT. Nabila Cahaya Abadi especially in terms of administration and cost performance. Although usage is not always high, the use of Recruitment has provided many conveniences, especially for recruiters. it is an example of real implementation of the use of technology that is effective and environmentally friendly to assist the HR function in the company. The conclusion that can be drawn from this research is that the automation of human assistance management functions into internet-based devices requires strategic integration of human resource control with corporate methods, corporate forms and ways of life. To support this, PT. Nabila Cahaya Abadi prioritizes education and coaching so that it will form a first-class company that is ready for exchange management.